Efficacy of Antibodies and Antiviral Drugs against Omicron BA.2.12.1, BA.4, and BA.5 Subvariants - Takashita, Emi; Yamayoshi, Seiya; Simon, Viviana; van Bakel, Harm; Sordillo, Emilia M.; Pekosz, Andrew; Fukushi, Shuetsu; Suzuki, Tadaki; Maeda, Ken; Halfmann, Peter; Sakai-Tagawa, Yuko; Ito, Mutsumi; et al. (The New England journal of medicine, 2022)
In Vitro Activity of Antibodies and Drugs against OmicronIn this study, investigators who were evaluating in vitro neutralization of omicron subvariants by monoclonal antibodies and antiviral drugs found considerable variation among the agents.